Keeping poultry houses free of disease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Wilfred Allo Nkumbuh explains to Martha Chindong how, by keeping strict rules, he prevents the spread of disease on his poultry farm in Cameroon.